Built environment overseas exposure for architectural students of IIUM - Mohd Nawawi, Norwina ([s.n.], 2000)
A working paper as a clarification on the need for overseas travel for programme of architecture in both BSc Architectural Studies (Part 1) and Bachelor of Architecture (Part 2) degree level.